Autophagy controls the pathogenicity of OPA1 mutations in dominant optic atrophy. Issue 10 (4th April 2017) - Kane, Mariame Selma; Alban, Jennifer; Desquiret‐Dumas, Valérie; Gueguen, Naïg; Ishak, Layal; Ferre, Marc; Amati‐Bonneau, Patrizia; Procaccio, Vincent; Bonneau, Dominique; Lenaers, Guy; Reynier, Pascal; Chevrollier, Arnaud
Abstract: Optic Atrophy 1 (OPA1) gene mutations cause diseases ranging from isolated dominant optic atrophy (DOA) to various multisystemic disorders. OPA1, a large GTPase belonging to the dynamin family, is involved in mitochondrial network dynamics. The majority of OPA1 mutations encodes truncated forms of the protein and causes DOA through haploinsufficiency, whereas missense OPA1 mutations are predicted to cause disease through deleterious dominant‐negative mechanisms. We used 3D imaging and biochemical analysis to explore autophagy and mitophagy in fibroblasts from seven patients harbouring OPA1 mutations. We report new genotype–phenotype correlations between various types of OPA1 mutation and mitophagy. Fibroblasts bearing dominant‐negative OPA1 mutations showed increased autophagy and mitophagy in response to uncoupled oxidative phosphorylation. In contrast, OPA1 haploinsufficiency was correlated with a substantial reduction in mitochondrial turnover and autophagy, unless subjected to experimental mitochondrial injury. Our results indicate distinct alterations of mitochondrial physiology and turnover in cells with OPA1 mutations, suggesting that the level and profile of OPA1 may regulate the rate of mitophagy.